The Turkish wheat market: spatial price transmission and the impact of transaction costs - Stephan Brosig; Thomas Glauben; Linde Götz; Enno-Burghard Weitzel; Ahmet Bayaner (Agribusiness, 2011)
Agricultural production is spread all over Turkey and the considerably different climatic and topographical conditions among the provinces lead to highly diversified agricultural production. Therefore, is it reasonable to assume an integrated market all over Turkey? The authors analyze spatial price transmission among 28 Turkish provinces with regard to wheat markets. They apply a bivariate threshold vector error correction model with two symmetric thresholds to account for transaction costs. They find an inner cluster of highly integrated provinces and identify the market size as a driving force of market integration. Furthermore, this study is unique in determining the minimum level of transaction costs. The results suggest that the minimum transaction costs impede full market integration more often on smaller than on larger markets. [EconLit citations: L100; D230; Q110]. 2010 Wiley Periodicals, Inc.
Keywords: L100; D230; Q110; 330; Turkey; market integration; threshold vector error correction; new economic geography; transaction costs